Chapter 7 Organizational and Cultural Transformations to Benefit Pregnant People and Mothers in Dance - Duffy, Ali (Taylor & Francis, 2023)
Based on the data collected from participants and through analyzing scholarship and perspectives from popular culture, Chapter VII offers recommendations for institutional and organizational change that would be supportive of mothers in dance. The chapter first summarizes major issues as emergent in the data. Then, participant perspectives reveal possibilities for improved working conditions through revised policy and law; ideas to create equitable and fair workplaces, including new models of dance organizations to encompass the needs of all; and best practices for creating opportunities for pregnant people and mothers to coexist with and thrive in dance organizations among supervisors and colleagues with and without children.